2012
DOI: 10.1126/scitranslmed.3003008
|View full text |Cite
|
Sign up to set email alerts
|

Skin Effector Memory T Cells Do Not Recirculate and Provide Immune Protection in Alemtuzumab-Treated CTCL Patients

Abstract: CTCL is a cancer of skin homing T cells with variants that include leukemic CTCL (L-CTCL), a malignancy of central memory T cells (TCM), and mycosis fungoides (MF), a malignancy of skin resident effector memory T cells (TEM). We report that low-dose alemtuzumab (αCD52) effectively treated patients with refractory L-CTCL but not MF. Alemtuzumab depleted all T cells in blood and depleted both benign and malignant TCM from skin, but a diverse population of skin resident TEM remained in skin after therapy. T-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
323
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(342 citation statements)
references
References 47 publications
13
323
0
6
Order By: Relevance
“…However, the possibility of migration to the draining LN (but not recirculation to other tissues) following Ag stimulation was not excluded, especially for CD4 + T cells, and indeed, it is reported that some patients with malignant disease of effector memory T cells (mycosis fungoides) can develop LN involvement (28). Our data confirm that the majority of skin-tropic T cells in the blood during noninflammatory conditions are of the central memory type.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the possibility of migration to the draining LN (but not recirculation to other tissues) following Ag stimulation was not excluded, especially for CD4 + T cells, and indeed, it is reported that some patients with malignant disease of effector memory T cells (mycosis fungoides) can develop LN involvement (28). Our data confirm that the majority of skin-tropic T cells in the blood during noninflammatory conditions are of the central memory type.…”
Section: Discussionsupporting
confidence: 77%
“…Evidence from murine experiments and studies of T cell depletion in human skin T cell malignancies (leukemic CTCL and mycosis fungoides) suggest that central memory T cells from skin regularly recirculate, whereas this is not the case for skin effector memory cells (28,29). However, the possibility of migration to the draining LN (but not recirculation to other tissues) following Ag stimulation was not excluded, especially for CD4 + T cells, and indeed, it is reported that some patients with malignant disease of effector memory T cells (mycosis fungoides) can develop LN involvement (28).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are somewhat difficult to reconcile with the present finding that only a small proportion of the dermal Tregs are actively migratory. Recent studies in humans and mice provide evidence that the skin is a major reservoir of nonrecirculating, resident effector memory T cells (9,(31)(32)(33). These resident cells are thought to serve important functions in controlling local immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, they subsequently underwent a rapid homeostatic proliferation, which at month 1 led to an increased percentage of CD4 + and CD8 + memory cells in comparison with baseline. Following nearly complete depletion, memory cells preferentially expanded owing to their homeostatic proliferation, the conversion of naive cells to the memory phenotype, decreased requirements for high Ag dose and costimulatory signals for activation, as well as preferential survival in peripheral lymphoid organs from which they can repopulate the peripheral circulation (32,33).…”
Section: Discussionmentioning
confidence: 99%